2014
DOI: 10.1136/bmjopen-2014-005757
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic use, pain and daytime sedation in people with and without dementia in aged care facilities: a cross-sectional, multisite, epidemiological study protocol

Abstract: IntroductionPeople living with dementia may experience and express pain in different ways to people without dementia. People with dementia are typically prescribed fewer analgesics than people without dementia indicating a potential difference in how pain is identified and treated in these populations. The objectives of this study are to (1) investigate the prevalence of analgesic load, pain and daytime sedation in people with and without dementia in Australian residential aged care facilities (RACFs), and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Finish study involving 67 215 community-dwelling persons diagnosed with AD and 67 215 matched comparison persons without AD found that fewer people with AD used NSAIDs compared with people without AD (13.2% vs. 17.3%, respectively), which is in line with our findings 35. Underrecognition of pain and fear of adverse drug events due to NSAIDs might account for a lower prevalence of analgesic use in people with dementia 36. The main strength of this study was the whole-population coverage of people dispensed medicines for dementia and an inclusion of a matched comparison cohort of people not dispensed medicines for dementia.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Finish study involving 67 215 community-dwelling persons diagnosed with AD and 67 215 matched comparison persons without AD found that fewer people with AD used NSAIDs compared with people without AD (13.2% vs. 17.3%, respectively), which is in line with our findings 35. Underrecognition of pain and fear of adverse drug events due to NSAIDs might account for a lower prevalence of analgesic use in people with dementia 36. The main strength of this study was the whole-population coverage of people dispensed medicines for dementia and an inclusion of a matched comparison cohort of people not dispensed medicines for dementia.…”
supporting
confidence: 89%
“…35 Underrecognition of pain and fear of adverse drug events due to NSAIDs might account for a lower prevalence of analgesic use in people with dementia. 36 The main strength of this study was the whole-population coverage of people dispensed medicines for dementia and an inclusion of a matched comparison cohort of people not dispensed medicines for dementia. However, there are some limitations in this study.…”
Section: Prevalence Of Individual Stopp Criteriamentioning
confidence: 99%
“…The Neuropsychiatric Inventory—Nursing Home (NPI‐NH) version was used to assess residents' neuropsychiatric symptoms using the frequency and severity questions of the behavioral domains of the scale and professional caregiver burden using the disruptiveness question for each behavioral domain of the scale. Details of scales used have been published previously . A total score was calculated for each scale, and those scoring in the lowest (satisfaction, quality‐of‐life) or highest (neuropsychiatric symptom, disruptiveness) quartiles were identified as reporting a deficit in this scale.…”
Section: Methodsmentioning
confidence: 99%
“…RACFs were classified according to level of support: ranging from aided daily tasks and personal care in low-level RACFs to 24-h nursing in high-level RACFs. The full study protocol has been described previously [18]. …”
Section: Methodsmentioning
confidence: 99%
“…A standard data extraction form, comprising a series of validated and widely used data collection scales, enabled collection of other clinical data. Both resident self-report and observational scales completed by staff informants were utilized [18]. Where possible, residents chose the most appropriate response through verbal or written communication.…”
Section: Methodsmentioning
confidence: 99%